Mahasiswa dan telefon selular: Sejauh manakah penerimaan terhadapnya - Ismail, Syamsul Anuar; Ishak, Mohd Sobhi (2004)
This paper examines the acceptance of the mobile phone usage among the graduates. The objective of the study was to identify factors that encouraged the usage of the mobile phone among the graduates, as well as to examine their attitude towards this acceptance on the usage of the mobile phone. The framework of the study is based on the Technology Acceptance Model (TAM) by Davis (1989). A total of 389 graduates from the Universiti Utara Malaysia participated in the study. A questionnaire was used to collect the data. The findings showed that factors like portability in terms of its weight, size and having the current trend and ofering interesting service packages managed to encourage the usage of the mobile phone among graduates. Further more, its affordable and comparatively cheaper price as well as certain features available like sending and receiving SMS on the mobile phone were also among the factors that encouraged the usage. To be able to get in touch at any time of emergency and troubles were also factors that encouraged the usage of the mobile phone among graduates whereas, the acceptance of the usage among graduates were encouraged by the perceptions that the mobile phone is 1) something which is handy 2) something which is useful 3)something which is entertaining and 4) something they can show off.